Development of the evaluation model of technological parameters of shaping workpieces from powder materials - Iskovych-Lototsky, Rostislav; Zelinska, Oksana; Ivanchuk, Yaroslav; Veselovska, Natalia (Eastern-European Journal of Enterprise Technologies, 2017)
High efficiency of the technological process of shaping workpieces from powder materials using vibratory and vibro-impact treatments was defined. High degree of intensification of the process of workpiece sealing is achieved using original inertial vibration press-hammers with hydropulse drive. The explored systematic approach to technological process of shaping (process, machine, and workpiece) and sets of design parameters of technological equipment allowed us to create a mathematical model of determining average density of a workpiece. Extremum of array of values of membership function as a determinant of completeness and effectiveness, was selected as the criterion of estimation of functioning efficiency of technological process of shaping workpieces Assessment of efficiency of functioning of technological complex was made based on fuzzy sets. Relationships between parameters of average density of a workpiece and function of the mode of vìbroimpact loading of a workpiece were defined. Performed analysis of technological parameters of workpieces demonstrated adequacy of the developed complex mathematical apparatus for evaluation of dynamic changes in average density and uneven density of derived products. Expediency of time restriction of shaping a final product by vibroimpact pressing method for quality maintaining was established. Development of a promising method of evaluation of production complex condition based on vibropress equipment with hydropulse drive will allow an increase in efficiency of the technological process of shaping workpieces from powder materials.